Sub‐micrometer focusing setup for high‐pressure crystallography at the Extreme Conditions beamline at PETRA III. (5th April 2022) - Glazyrin, K.; Khandarkhaeva, S.; Fedotenko, T.; Dong, W.; Laniel, D.; Seiboth, F.; Schropp, A.; Garrevoet, J.; Brückner, D.; Falkenberg, G.; Kubec, A.; David, C.; et al.
Abstract : Facing the challenges of X‐ray diffraction from tiny samples subjected to multimegabar pressures, instrumentation developments are presented that enable, among other studies, single‐crystal data collection from micrometer‐ to sub‐micrometer‐sized grains. The developments are based on a sub‐micrometer beam capability employing compound refractive lenses operating with a phase correcting plate and a precise motorization solution. Abstract : Scientific tasks aimed at decoding and characterizing complex systems and processes at high pressures set new challenges for modern X‐ray diffraction instrumentation in terms of X‐ray flux, focal spot size and sample positioning. Presented here are new developments at the Extreme Conditions beamline (P02.2, PETRA III, DESY, Germany) that enable considerable improvements in data collection at very high pressures and small scattering volumes. In particular, the focusing of the X‐ray beam to the sub‐micrometer level is described, and control of the aberrations of the focusing compound refractive lenses is made possible with the implementation of a correcting phase plate. This device provides a significant enhancement of the signal‐to‐noise ratio by conditioning the beam shape profile at the focal spot. A new sample alignment system with a small sphere of confusion enables single‐crystal data collection from grains of micrometer to sub‐micrometer dimensions subjected to pressures as high as 200 GPa. The combination of the technical development of the optical path and the sample alignment system contributes to research and gives benefits on various levels, including rapid and accurate diffraction mapping of samples with sub‐micrometer resolution at multimegabar pressures.